Therapeutic effect of modified zengye decoction on primary Sjogren’s syndrome and its effect on plasma exosomal proteins - Zeng, Yimin; Peng, Xin; Wang, Yun; Hou, Lei; Ma, Wukai; Yang, Peng (Frontiers in Pharmacology, 2022)
Background: Modified Zengye Decoction (MZD), a traditional Chinese medicine, is an effective treatment for patients with primary Sjögren’s syndrome (pSS). Purpose: To evaluate the efficacy of MZD and investigate its effect on plasma exosomal proteins. Methods: Eighteen pSS patients were treated with MZD for 2 weeks. The therapeutic effect was evaluated by observing the changes in clinical symptoms, laboratory parameters, and plasma cytokines before and after treatment. Then, the differentially expressed proteins (DEPs) in the plasma exosomes before and after treatment were identified via label-free proteomics, while Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment were used to analyze the possible biological functions and signaling pathways involved in the exosomal DEPs. Results: MZD can effectively relieve the clinical symptoms of pSS patients, downregulate the plasma IgG and IgM levels, and inhibit plasma cytokine production. Thirteen DEPs were identified via label-free proteomics in the plasma exosomes before and after MZD treatment, of which 12 were downregulated proteins. GO analysis showed that these downregulated proteins were mainly related to the insulin response involved in dryness symptoms and the Gram-negative bacterial defense response and proteoglycan binding involved in infection. KEGG enrichment analysis showed that these downregulated proteins were primarily associated with the porphyrin metabolism involved in oteoarthrosis and the NF-κB and TLR4 pathways involved in infection. Conclusion: MZD can effectively alleviate SS symptoms, while its mechanism may be associated with the reduced protein expression in insulin response, porphyrin metabolism, and the TLR4/NF-κB pathway.